2022
DOI: 10.1002/pc.26674
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tannic acid functional multi‐walled carbon nanotubes on the properties of nitrile rubber/ethylene propylene diene monomer composites

Abstract: Multi‐walled carbon nanotubes (MWCNT) were first non‐covalently functioned by tannic acid (TA), then blended with nitrile rubber (NBR) and ethylene propylene diene monomer (EPDM) with NBR:EPDM:TA‐MWCNT = 70:30:5. TA‐MWCNT and the composites had been characterized by various techniques, including Fourier transform infrared spectroscopy (FT‐IR), Raman analysis, transmission electron microscopy (TEM), mechanical properties testing, thermal‐oxidative aging testing, differential scanning calorimetry (DSC), dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…With the incorporation of different carbon nanoparticles, improved thermal stability was observed. From the inset picture of Figure 9a, it can be observed that the thermal stability for the composites is in the order of GR > CN > CB > FU, which is consistent with the reported investigation [39][40][41][42]. This can be assigned to the different interfacial interactions and surface areas of the nanoparticles, which can form an efficient tortuous path effect with SIS to prevent the degradation of the nanocomposite.…”
Section: Thermal Stabilitysupporting
confidence: 87%
“…With the incorporation of different carbon nanoparticles, improved thermal stability was observed. From the inset picture of Figure 9a, it can be observed that the thermal stability for the composites is in the order of GR > CN > CB > FU, which is consistent with the reported investigation [39][40][41][42]. This can be assigned to the different interfacial interactions and surface areas of the nanoparticles, which can form an efficient tortuous path effect with SIS to prevent the degradation of the nanocomposite.…”
Section: Thermal Stabilitysupporting
confidence: 87%
“…It is a promising channel to prepare the high‐performance rubber composites by nanofiller, such as nano marble, 12 nano silica, graphene, hydrotalcite, carbon nanotubes, zirconium phosphate and so on 13–15 . These nanofillers with excellent properties can make outstanding contributions to certain aspects of rubber properties such as mechanical properties, 16,17 thermal stability 18,19 and aging resistance 20 . However, in general, the elasticity of rubber will be greatly reduced after adding with the reinforced nanofillers 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…[28] At the same time, the introduction of a reinforcing filler has been proven to enhance the elastic modulus and hardness of the matrix for both states. [29][30][31][32][33] Papadopoulos et al studied the effect of various inclusions (MMT, Graphene nanoplatelets, CNTs, and Halloysite) and showed that incorporating any of the aforementioned fillers improved elastic modulus and hardness. [34] Similar findings were reported by Klonos et al regarding the nanomechanical behavior of PBF filled with 1 wt% of MMT and functionalized MMT.…”
Section: Introductionmentioning
confidence: 99%